2022
DOI: 10.3390/ijerph19159657
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Information Disclosure, Digital Transformation, and Total Factor Productivity: Evidence from Chinese Heavy Polluting Listed Companies

Abstract: Environmental information disclosure, as a new environmental regulatory model, is important for achieving collaborative environmental pollution management and sustainable socioeconomic development. Based on the data of listed firms in China’s A-share heavy pollution industry from 2009 to 2019, this paper empirically tested the impact of environmental information disclosure on the total factor productivity of enterprises and the contribution of digital transformation to this impact. An increase in the level of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 45 publications
0
1
0
Order By: Relevance
“…Ren, Y et al [8] believe that the digital transformation of new energy enterprises can promote improvements in total factor productivity by improving enterprise operation efficiency, reducing costs, and enhancing innovation. Liu, H et al [39] found that both digital transformation and environmental information disclosure of heavily polluting enterprises can improve total factor productivity, and there is a substitution effect. Li, N et al [40] found that the ESG performance of manufacturing enterprises plays a positive moderating role in the relationship between digital transformation and total factor productivity.…”
Section: The Effect and Mechanism Of Digital Transformation On Total ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Ren, Y et al [8] believe that the digital transformation of new energy enterprises can promote improvements in total factor productivity by improving enterprise operation efficiency, reducing costs, and enhancing innovation. Liu, H et al [39] found that both digital transformation and environmental information disclosure of heavily polluting enterprises can improve total factor productivity, and there is a substitution effect. Li, N et al [40] found that the ESG performance of manufacturing enterprises plays a positive moderating role in the relationship between digital transformation and total factor productivity.…”
Section: The Effect and Mechanism Of Digital Transformation On Total ...mentioning
confidence: 99%
“…Second, this study found that an increase in analysts' attention to enterprises has a significant positive impact on total factor productivity, enriching the research on the influencing factors of total factor productivity. Third, most scholars have studied the mechanism of digital transformation's impact on total factor productivity from the perspective of enterprises' internal characteristics [8][9][10]39,40], without discussing whether analysts focus on playing a role in the process of digital transformation and affecting total factor productivity. In order to fill this theoretical gap, this study, for the first time, incorporated digital transformation, analysts' attention, and total factor productivity into the same theoretical framework, laying the foundation for the information intermediary role of analysts' attention between digital transformation and total factor productivity, and broadening the research on the impact of digital transformation on total factor productivity from the perspective of analysts' attention.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…(1) From the perspective of enterprises, high‐tech enterprises, non‐heavily polluting enterprises, central board‐listed enterprises, GEM enterprises, and enterprises in economically developed regions positively affect digital transformation (Peng et al, 2022; Wu et al, 2022). (2) From the standpoint of enterprise operations, the business model, organizational structure, cost control, operating performance, profitability, innovation efficiency, corporate value, and social responsibility significantly affect EDT (Homburg & Wielgos, 2022; Liu et al, 2022; Ma et al, 2022; Teng et al, 2022; Wang & Chen, 2022). (3) From the perspective of corporate governance, board resources, board willingness, executive age, executive gender, executive education, executive nationality, executive political affiliation, and equity concentration significantly affect EDT (Ceipek et al, 2021; Chen & Hao, 2022).…”
Section: Literature Analysis and Hypothesesmentioning
confidence: 99%